The Sexual Violence Criminal Law (TPKS Law) in Preserving The Family in The Maqasid Sharia Perspective - Suwarjin Suwarjin (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2023)
This study aims to reveal the facts of the forms of sexual violence that occurred in Bengkulu and then to describe the urgency of the Law on Sexual Violence in protecting the family from a maqasid sharia perspective. This type of research is qualitative research library research with a normative-conceptual approach. The results of this study are (1) The ratification of the Sexual Violence Law is an effort to renew the law in protecting victims of sexual Violence, which has not previously been regulated in specific laws. Bengkulu ranks fourth in the highest cases of sexual Violence on the island of Sumatra, and the perpetrators are dominated by those closest to them. In Bengkulu, there is no support for sustainable psychosocial recovery in the form of educational support, psychological services, reproductive health examination and care services, and support for potential and talent development for child victims. The unavailability of safe houses for victims of Violence has forced social workers to choose orphanages as an alternative. (2) The urgency of the Law on Sexual Violence in protecting the family from the maqasid sharia perspective is at the dharuriyat level, namely aiming to protect or protect religion (Hifz al-Diin) protect the body and soul (Hifz al-Nafs) Protect the mind (Hifzula'ql) ) Protecting offspring (Hifz al-Nasl) Penelitian ini bertujuan untuk mengungkap fakta bentuk-bentuk kekerasan seksual yang terjadi di Bengkulu kemudian mendeskripsikan urgensi UU Kekerasan Seksual dalam melindungi keluarga dari perspektif maqasid syariah. Jenis penelitian ini adalah penelitian kualitatif library research dengan pendekatan normatif-konseptual. Hasil penelitian ini adalah (1) Pengesahan UU Kekerasan Seksual merupakan upaya pembaharuan hukum dalam melindungi korban Kekerasan seksual yang sebelumnya tidak diatur dalam undang-undang khusus. Bengkulu menempati urutan keempat kasus kekerasan seksual tertinggi di Pulau Sumatera, dan pelakunya didominasi oleh orang-orang terdekatnya. Di Bengkulu, belum ada dukungan pemulihan psikososial berkelanjutan berupa dukungan pendidikan, layanan psikologis, layanan pemeriksaan dan perawatan kesehatan reproduksi, serta dukungan pengembangan potensi dan bakat anak korban. Tidak tersedianya rumah aman bagi korban kekerasan memaksa para pekerja sosial memilih panti asuhan sebagai alternatif. (2) Urgensi UU Kekerasan Seksual dalam melindungi keluarga dari perspektif maqasid syariah adalah pada tataran dharuriyat yaitu bertujuan untuk menjaga atau melindungi agama (Hifz al-Diin), melindungi jiwa dan raga (Hifz al-Nafs), Melindungi akal (Hifzula'ql), dan Melindungi keturunan (Hifz al-Nasl)